Dynamic evolution of ceftazidime–avibactam resistance due to interchanges between blaKPC-2 and blaKPC-145 during treatment of Klebsiella pneumoniae infection - Chen, Yili; Yang, Runshi; Guo, Penghao; Liu, Pingjuan; Deng, Jiankai; Wu, Zhongwen; Wu, Qingping; Huang, Junqi; Liao, Kang (Frontiers in Cellular and Infection Microbiology, 2023)
Background The emergence of ceftazidime-avibactam (CZA) resistance among carbapenem-resistant Klebsiella pneumoniae (CRKP) is of major concern due to limited therapeutic options. Methods In this study, ten CRKP strains were isolated from different samples of a patient with CRKP infection receiving CZA treatment. Whole-genome sequencing (WGS) and conjugation experiments were performed to determine the transferability of carbapenem resistance gene. Results This infection began with a KPC-2-producing K. pneumoniae (CZA MIC=2μg/mL, imipenem MIC≥16μg/mL). After 20 days of CZA treatment, the strains switched to amino acid substitution of T263A caused by a novel KPC-producing gene, blaKPC-145，which restored carbapenem susceptibility but showed CZA resistance (CZA MIC≥256μg/mL, imipenem MIC=1μg/mL). The blaKPC-145 gene was located on a 148,185 bp untransformable IncFII-type plasmid. The subsequent use of carbapenem against KPC-145-producing K. pneumoniae infection led to a reversion of KPC-2 producer (CZA MIC=2μg/mL, imipenem MIC≥16μg/mL). WGS analysis showed that all isolates belonged to ST11-KL47 and the number of SNPs was 14. This implied that these blaKPC-positive K. pneumoniae isolates might originate from a single clone and have been colonized for a long time during the 120 days treatment period. Conclusion This is the first report of CZA resistance caused by blaKPC-145, which emerged during the treatment with CZA against blaKPC-2-positive K. pneumoniae associated infection in China. These findings indicated that the routine testing for antibiotics susceptibility and carbapenemase genotype are very essential during CZA treatment.